Revitalisasi Nilai-Nilai Tasawuf sebagai Landasan Pendidikan Moral di Era Disrupsi - Waluyo Erry Wahyudi (Journal of Literature Review, 2025)
The disruption era is marked by rapid social, cultural, and technological changes, often leading to a moral crisis across various levels of society. In this context, Sufi values such as sincerity, simplicity, self-reflection, and compassion are highly relevant as a foundation for moral education. This article aims to revitalize Sufi values within the educational system as a solution to contemporary moral challenges. Using a qualitative-descriptive approach and literature review, the study reveals that integrating Sufi values into education can shape individuals who are spiritual, ethical, and possess strong integrity. This revitalization serves as a crucial strategy to strengthen the moral character of the younger generation amidst modernization and globalization.